SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA PENINGKATAN PRESTASI AKADEMIK MENGGUNAKAN METODE PREFERENCE SELECTION INDEX - Rizal Tjut Adek; Hafizh Al Kautsar Aidilof; Ali Imran Nasution (Jurnal Teknoinfo, 2022)
The rapid development of information technology is in line with the development of computational methods that help solve various problems, one of which is the method of decision support systems. Higher education institutions, especially Malikussaleh University, have many scholarship programs like the Academic Achievement Improvement Scholarship or PPA. PPA is a scholarship that has existed since 2012 which was launched and allocated by the Ministry of Research, Technology and Higher Education with a focus on aspects of improving academic achievement. However, the selection system is still conventional or manual, so it takes longer. This study aims to implement a decision-making system in an application to recommend PPA scholarship recipients automatically. The existence of an automatic decision-making system will be more efficient and effective to help speed up the process of making decisions based on the criteria they have. Some of the assessment criteria used include GPA, semester, the total income of parents, and the number of dependents of parents. Also, the alternative data used are 825 data. The method applied to the system is the Preference Selection Index (PSI) method, which is used as a reference for ranking results and measuring accuracy. In this method, it is not necessary to determine the relative importance between the criteria. In addition, this method does not have certain conditions that require calculating the weight of the related criteria in decision-making problems. The research steps used are the waterfall model with several main stages, namely planning, modeling, implementation, and testing. This system is built using PHP as the programming language and MySQL as the database. Based on system testing, it is found that the system is following the design and can provide ranking results in the form of recommendations for scholarship recipients with a comparison of stakeholder decisions and that the system using the PSI method is 66%. The PSI method can be implemented by displaying each alternative's most considerable PSI value by displaying the ranking results. This PPA Scholarship Acceptance DSS application can be used as an alternative to making it easier for related parties to determine who is entitled to receive the scholarship.